Multidisciplinary optimisation of a CFRP wing cover - Phillips, Benjamin John (Cranfield University, 2009)
With the market introduction of both the Airbus A350XWB and the Boeing 787, Carbon Fibre Reinforced Plastics (CFRP) has been applied to primary structure of large commercial aircraft, as a means of enhancing overall performance. Both these aircraft are being developed and produced in a unique way where Airbus and Boeing are acting as System Integrators and using Risk Sharing Partners to develop the majority of the principal components. To support this new business and technological model it is necessary that the System Integrator has sufficient knowledge and tools to support the development of the components. Of particular interest are items such as the wing covers, as they are both heavy and expensive items, thus offering large opportunities for optimisation, in particular when the benefits of applying CFRP are considered. This creates the forum for this thesis, i.e. to thoroughly understand all factors that influence a CFRP wing cover, from which an optimisation methodology is developed, incorporating design constraints, while seeking the lightest weight solution, with a resultant Life Cycle Cost (LCC). Based on this, different solutions can be compared based on weight and LCC. In general stringer-stiffened panels are, from a weight perspective, the optimal configuration for wing covers, and thus are solely considered. Serendipitously, due to their prismatic shapes, buckling calculations of stringer-stiffened panels can be solved with reasonable accuracy and ease using the Finite Strip Method (FSM), as opposed to more time consuming methods such as the Finite Element Method. A suitable FSM program is available from ESDU, which when used in combination with a configured Excel spreadsheet can take into consideration constraints established from the extensive literature review. Once the lowest weight solution is obtained under buckling constraints, the solution is then checked for in-plane and if desired out-of-plane strength. Based on the structurally optimised wing cover, the manufacturing cost is calculated using a Process Based Cost Model (PBCM), which has been developed based on different CFRP materials for the skin and stringer fabrication, as well as suitable manufacturing and integration methods. In order to consider the LCC, i.e. all costs from cradle to grave, the PBCM factors in both the cost of recycling scrap material during manufacture and after retirement. Furthermore, when more than one solution is compared then the Economic Value of Weight Saving, which is based on the range equation, can be factored in to consider the financial benefit of weight saving. The optimisation methodology and PBCM has been evaluated on diverse wing cover examples, which has considered both uni-directional prepreg, non-crimp fabric and braids materials in combination with autoclave and liquid composite moulding techniques. The results demonstrated a trend which can be considered realistic, although the cost estimation is very much dependent on the assumptions made. In conclusion, the thesis and the optimisation methodology can be used to compare different configurations.